Efficacy of azilsartan medoxomil with chlorthalidone in hypertension. (July 2014) - Baker, William L; Nigro, Stefanie C; White, William B
<x xml:space="preserve">Abstract</x> Azilsartan medoxomil (AZL) is the most recently approved angiotensin receptor blocker (ARB) for treating patients with hypertension. A fixed-dose combination product with AZL and the thiazide-like diuretic chlorthalidone (CLD) is now available to treat individuals who require additional blood pressure lowering. For this review, a literature search was conducted using MEDLINE and the keywords and MeSH terms azilsartan, azilsartan medoxomil, chlorthalidone, thiazide, blood pressure and hypertension. References for retrieved articles were also scanned for relevant citations. No language restrictions were used. AZL is structurally related to candesartan and has been shown to provide more potent angiotensin receptor antagonism versus other ARBs. CLD is a thiazide-like diuretic with a longer half-life and greater blood pressure lowering efficacy than hydrochlorothiazide. The combination of AZL plus CLD has superior efficacy to other ARBs alone or in combination with hydrochlorothiazide based on extensive evaluation in clinical trials. This superior efficacy is not offset by a large imbalance in clinically important adverse events.